2013
DOI: 10.1039/c2cs35343a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal engineering of topochemical solid state reactions

Abstract: Solid state reactions offer a unique opportunity for synthesizing complex molecules with amazing regio- and stereo-specificity otherwise difficult to synthesize by conventional organic synthetic methodologies. In particular, the solid state [2 + 2] reaction is a well studied reaction in terms of a crystal engineering perspective. The main challenge in performing solid state reactions is bringing the molecules into reactive orientations such that the reactive groups are within a certain proximal distance. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
315
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(320 citation statements)
references
References 119 publications
2
315
0
3
Order By: Relevance
“…A key requirement for effective supramolecular synthesis and crystal engineering, 14 is a detailed understanding of the structural 35 balance between different synthons, and therefore it is important to establish how potentially competing interactions will manifest themselves in the solid state. It has previously been shown that both cyanooxime moieties 15 and phenolic -OH groups 16 are more effective hydrogen-bond donors than carboxylic acids.…”
Section: Scheme 1 the Oxime Moietymentioning
confidence: 99%
“…A key requirement for effective supramolecular synthesis and crystal engineering, 14 is a detailed understanding of the structural 35 balance between different synthons, and therefore it is important to establish how potentially competing interactions will manifest themselves in the solid state. It has previously been shown that both cyanooxime moieties 15 and phenolic -OH groups 16 are more effective hydrogen-bond donors than carboxylic acids.…”
Section: Scheme 1 the Oxime Moietymentioning
confidence: 99%
“…Up to date, this subject has been highly developed. The advances in supramolecular crystal engineering and improvements of our understanding about intermolecular interactions have enabled chemists to construct solids with predetermined physical properties for solid state reactions [93,94]. The solid state reactions have the advantages of solvent-free conditions that related to green chemistry and stereo-specific reactions with high yields.…”
Section: Crystal Engineering Of Solid State Photochemical Reactionsmentioning
confidence: 99%
“…The classical work of G. Schmidt and coworkers in 1960s paved away the field of solidstate organic photochemistry as well as crystal engineering [12][13][14]. Due to this historical importance, this double bonds containing spacer and terminal ligands have been incorporated into coordination polymers (CPs) and porous CPs (PCPs) which is also popularly called as metal-organic frameworks (MOFs) to design photo-reactive solids [15][16][17]. The metal-coordination bond offers very important role in directing the organic linkers and/or guest molecules to satisfy the geometry criteria required for the photoreactions.…”
Section: Introductionmentioning
confidence: 99%